Challenging “Size Matters” Messages: An Exploration of the Experiences of Critical Obesity Scholars in Higher Education - Cameron, Erin Michelle (Canadian Journal of Higher Education, 2016)
Given that postsecondary institutions are increasingly seen as sites to promote health, critical scholars are calling attention to how the contemporary Western weight-centred health paradigm reinforces a “size matters” message that is fueling harmful attitudes towards and judgments of bodies. As such, research that highlights strategies to promote safe teaching and learning environments for students and faculty, regardless of body shape and size, is of utmost importance. Through 26 participant interviews, this study examines the experiences of critical obesity scholars who teach courses that engage critical approaches to obesity, fatness, and body size. The findings of this study shed light on the developing field of critical obesity scholarship, the types of challenges faced by critical obesity scholars in higher education, and how these scholars are building community as a way of coping with challenges facing the emerging field.